2007
DOI: 10.1159/000106100
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Bone Marrow Necrosis and Symptomatic Hypercalcemia in B Cell Blastic Transformation of Chronic Myeloid Leukemia: Report of a Case and Review of the Literature

Abstract: Extensive bone marrow necrosis and symptomatic hypercalcemia have been described independently as rare complications of chronic myeloid leukemia. Here we report a 66-year-old man who developed B cell blastic transformation 10 years after diagnosis of CML in the chronic phase. Extensive bone marrow necrosis and symptomatic hypercalcemia concurrently developed after transformation, with development of disseminated intravascular coagulation and multifocal osteolysis. Most necrotic cells were readily identifiable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 57 publications
0
19
0
2
Order By: Relevance
“…(2002) [25]35/F2 yearsBPPRED, pamidronateCyclophosphamide, DOX, VCRCR in 1 week; died 1 month laterMiyoshi et al . (2005) [14]68/F4 yearsBPPRED, diuretic, incadronate, elcatoninEnocitabine, DAU, VCRCR; died 8 months laterNoguchi and Oshimi (2007) [26]66/M10 yearsBPHydration, PRED, bisphosphonate, elcatoninVCRCR in 3 weeks; died 8 weeks after admissionValizadeh et al . (2013) [18]70/MNRBPParathyroidectomyImatinibNRToro-Tobón et al .…”
Section: Discussionmentioning
confidence: 99%
“…(2002) [25]35/F2 yearsBPPRED, pamidronateCyclophosphamide, DOX, VCRCR in 1 week; died 1 month laterMiyoshi et al . (2005) [14]68/F4 yearsBPPRED, diuretic, incadronate, elcatoninEnocitabine, DAU, VCRCR; died 8 months laterNoguchi and Oshimi (2007) [26]66/M10 yearsBPHydration, PRED, bisphosphonate, elcatoninVCRCR in 3 weeks; died 8 weeks after admissionValizadeh et al . (2013) [18]70/MNRBPParathyroidectomyImatinibNRToro-Tobón et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our extensive literature search found over 30 reported cases, most of which were last reviewed in 2007 [8]. Among the published results, the median participant age at presentation was 44 years.…”
Section: Discussionmentioning
confidence: 99%
“…It can be produced and released not only from tumor cells but from normal tissue and act on PTH receptors [2,6,9]. This polypeptide, in a similar fashion to PTH, is implicated in hypercalcemia by stimulating bone resorption and increasing renal calcium reabsorption, and releasing calcium into serum [8,9,12,13]. Although not commonly elevated in hematological malignancies [9], previous studies have demonstrated elevated mRNA for PTHrP in cultured leukemic cells, as well as increased plasma levels in patients with T-cell leukemia and B-cell lymphoma [7,8,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow necrosis in CML has been reported in at least 14 patients, most of whom were in the blastic phase. 28 The necrosis results from cellular hypoxia due to ischemia of marrow microcirculation as a consequence of inflammatory damage or mechanical obstruction. 29 Bone marrow necrosis has also been associated with the use of imatinib mesylate.…”
Section: Discussionmentioning
confidence: 99%